2019
DOI: 10.20964/2019.12.21
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development of Metal Alloy Nanostructures for Electrochemical Hydrogen Generation

Abstract: Alkaline electrolytic water hydrogen production is an important method for large-scale industrialized hydrogen production. Research and development of new cathode electrode materials with lower hydrogen evolution overpotential and higher hydrogen evolution catalytic activity has become an important means to solve the problem of high energy consumption and low efficiency in electrochemical hydrogen generation. At present, alloys have been proven to be the best catalytic material for hydrogen evolution from elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…Precious metals (such as Pt [8] and Pd [9]) and precious metal oxides (such as IrO 2 [10] and RuO 2 [11]) are excellent electrocatalysts for hydrogen and oxygen evolution reactions, but their high cost and scarce sources limit their wide application in electrochemical water splitting. The low-cost transition metal-based electrocatalysts with both hydrogen and oxygen evolution reaction functions have attracted great interest in research [12], such as transition metal phosphides [13], hydroxides [14], sulfides [15], carbides [16], and metal alloys [17] being examples. However, there are still some problems with transition metal-based catalysts, such as high oxygen evolution overpotential, poor stability, mismatching of hydrogen evolution/oxygen evolution reactivity, and low energy conversion efficiency [12,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Precious metals (such as Pt [8] and Pd [9]) and precious metal oxides (such as IrO 2 [10] and RuO 2 [11]) are excellent electrocatalysts for hydrogen and oxygen evolution reactions, but their high cost and scarce sources limit their wide application in electrochemical water splitting. The low-cost transition metal-based electrocatalysts with both hydrogen and oxygen evolution reaction functions have attracted great interest in research [12], such as transition metal phosphides [13], hydroxides [14], sulfides [15], carbides [16], and metal alloys [17] being examples. However, there are still some problems with transition metal-based catalysts, such as high oxygen evolution overpotential, poor stability, mismatching of hydrogen evolution/oxygen evolution reactivity, and low energy conversion efficiency [12,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Benefiting from the high stability of transition-metal-based materials under alkaline conditions, the electrocatalysts of alkaline water electrolysis can get rid of noble metals (such as Pt for HER; Ir and/or Ru for OER). , Up to now, numerous transition metal-based HER and OER electrocatalysts have been deeply and widely researched, including Fe-, Co-, and Ni-based alloys, oxides, hydroxides/oxyhydroxides, sulfides, phosphides, and the corresponding compounds. For industry applications in high current density operations, the Ni-based alloys and alloy-based compounds with high electroconductibility are appreciated, such as NiCo binary alloys for HER and NiFe alloys for OER. Liang et al found, for example, that the binder-free NiFe nanowire array-based OER electrode exhibited durable OER performance at a current density of 1000 mA cm –2 at an overpotential of only 258 mV . To further enhance the electrochemical performance of Ni-based binary alloys, the more complex ternary alloys, such as FeCoNi alloys, opened the possibility, because the incorporated atoms regulate the electronic structure, ad-/desorption energies, and specific surface areas to optimal electrocatalytic activity. Moreover, the feasible ratio of alloys might further enhance the electroactivity of alloy-based compounds. For instance, Yang et al discovered that the electronic structures of the FeCoNi alloys tuned intentionally between alloys and graphene via changing the alloys composition to enhance the HER and OER activity .…”
Section: Introductionmentioning
confidence: 99%
“…The main issue of these electrochemical cells is the high energy required enable the water splitting reaction [15][16][17]. The greatest energy losses are due to electrodes overpotential [18], which strongly depend on electrodes and electrocatalysts [19].…”
Section: Introductionmentioning
confidence: 99%